Implementation Of Total Quality Management To Improve The Poultry Feed Manufacturing Processes - Salloom A. Al-Juboori (European Scientific Journal, ESJ, 2016)
This work is aimed to apply the basic concepts of Total quality Management (TQM) on process improvement of feed mill plant and to show the practical benefits of implementation of these concepts to improve the feed quality of poultry feed manufacturing processes, which suffers from low quality feed in a poultry enterprise as a field study. A special focus is made on the use of the basic quality tools to improve the production process by increasing Pellet Durability Index (PDI), where the 10 days durability index of the product has been monitored and analyzed using cause-effect-diagram and control-charts techniques. The analysis shows clearly that the feed producers can be effectively improved their production processes, when the grinding was changed from 6 mm and 8 mm sieves to 3 mm and 4 mm sieves with a moisture of 12%, the improvement was about 13 to 14%.While when the moisture is raised from 12% to 17%, the PDI% has increased to about 6 to 8%. Consequently, these improvements will save money, materials and make their processes sustainable with high quality.